Impact of 18F-Fluciclovine PET/CT Findings on Failure-Free Survival in Biochemical Recurrence of Prostate Cancer Following Salvage Radiation Therapy. (8th April 2023) - Lawal, Ismaheel O.; Marcus, Charles; Schuster, David M.; Goyal, Subir; Adediran, Omotayo A.; Dhere, Vishal R.; Joshi, Shreyas S.; Abiodun-Ojo, Olayinka A.; Master, Viraj A.; Patel, Pretesh R.; Fielder, Bridget; Goodman, Mark; et al.
Abstract : Purpose: We aimed to evaluate the impact of 18 F-fluciclovine PET/CT imaging on failure-free survival (FFS) post–salvage radiotherapy (SRT) for prostate cancer (PCa) recurrence. Methods: Seventy-nine patients were recruited in a phase 2/3 clinical trial to undergo 18 F-fluciclovine PET/CT before SRT for PCa. Four patients with extrapelvic disease were excluded. All patients were followed up at regular intervals up to 48 months. Treatment failure was defined as a serum prostate-specific antigen level of ≥0.2 ng/mL above the nadir after SRT, confirmed with an additional measurement, requiring systemic treatment or clinical progression. Failure-free survival was computed and compared between patients grouped according to 18 F-fluciclovine PET/CT imaging findings. Results: Eighty percent (60/75) of patients had a positive finding on 18 F-fluciclovine PET/CT, of which 56.7% (34/60) had prostate bed-only uptake, whereas 43.3% (26/60) had pelvic nodal ± bed uptake. Following SRT, disease failure was detected in 36% (27/75) of patients. There was a significant difference in FFS between patients who had a positive versus negative scan (62.3% vs 92.9% [ P < 0.001] at 36 months and 59.4% vs 92.9% [ P < 0.001] at 48 months). Similarly, there was a significant difference in FFS between patients with uptake in pelvic nodes ± bed versus prostate bed only at 36 months (49.8% vs 70.7%; P = 0.003) and at 48 months (49.8% vs 65.6%; P = 0.040). Failure-free survival was also significantly higher in patients with either negative PET/CT or prostate bed-only disease versus those with pelvic nodal ± prostate bed disease at 36 (78% vs 49.8%, P < 0.001) and 48 months (74.4% vs 49.8%, P < 0.001). CONCLUSIONS: Findings on pre-SRT 18 F-fluciclovine PET/CT imaging, even when acted upon to optimize the treatment decisions and treatment planning, are predictive of post-SRT FFS in men who experience PCa recurrence after radical prostatectomy. A negative 18 F-fluciclovine PET/CT is most predictive of a lower risk of failure, whereas the presence of pelvic nodal recurrence portends a higher risk of SRT failure.